Genetic diversity of Ethiopian cowpea [Vigna unguiculata (L) Walp] genotypes using multivariate analyses - Walle, T.; Mekbib, Firew; Amsalu, B.; Gedil, Melaku A (2019)
Cowpea is a multipurpose pulse crop grown by poor farmers in marginal and drought prone areas of Ethiopia. Information on the extent of genetic variation in cowpea genotypes is crucial to identify diverse genotypes for crop improvement and for efficient utilization of the existing genetic resources. Therefore, the objectives of the study were to assess the extent and pattern of morphological diversity among cowpea genotypes and to identify the traits contributing to the genetic diversity using multivariate analyses. The field experiment was conducted using 324 genotypes at Melkassa Agricultural Research Center and Miesso sub-center during the2016 cropping season. The first seven principal components explained 77% of the total variation. Almost all tested traits were important contributors to the variability in the first PC. The cluster analysis based on quantitative traits revealed six distinct groups at 90% similarity level. The clustering of genotypes did not follow patterns of geographical origin, indicating no relationship between genetic and geographic distribution. The highest inter cluster D2 was recorded between cluster IV and cluster VI (D2=41.62 units). The range of intra and inter cluster distance was 6.08 to 22.72 units and 17.37 to 41.62 units, respectively. Hence, the high genetic distance exhibited within and among clusters has to be exploited via crossing and selection of the most divergent parents for future cowpea breeding program.